Key Points in 1989. (1st September 2017) - Unknown
Abstract : 'The public is not sufficiently aware of the impact of IT. This fact provided the focus of a strategic review panel - a BCS thinktank - to isolate specific areas where the Society could rectify this situation.' News, January 1989.